Comparative Study of RAINSMART and REDAC Module Experimental Findings and Applications in BIOECODS Technology - Awalluddin, Aliah Fawzia (IRC, 2019)
One of the factors that has been contribute greatly to the urban storm water management system and affecting the storm water quality into receiving waters are due to expanding urbanization and land use. Storm water should be properly managed in aspects of quality and quantity to improve sustainable ecosystem.